Presentation of viral antigen controlled by a gene in the major histocompatibility complex. - Cerundolo, V; Alexander, J; Anderson, K; Lamb, C; Cresswell, P; McMichael, A; Gotch, F; Townsend, A (1990)
We describe a mutant human cell line (LBL 721.174) that has lost a function required for presentation of intracellular viral antigens with class I molecules of the major histocompatibility complex (MHC), but retains the capacity to present defined epitopes as extracellular peptides. The cell also has a defect in the assembly and expression of class I MHC molecules, which we show can be restored by exposure of the cells to a peptide epitope. This phenotype suggests a defect in the association of intracellular antigen with class I molecules similar to that described for the murine mutant RMA-S (ref. 5), but in the present case the genetic defect can be mapped within the MHC locus on human chromosome 6.